Reducing the Nitrate Content in Vegetables Through Joint Regulation of Short-Distance Distribution and Long-Distance Transport - Liang, Guihong; Zhang, Zhenhua (Frontiers in Plant Science, 2020)
As an important nitrogen source, nitrate (NO3−) absorbed by plants is carried throughout the plant via short-distance distribution (cytoplasm to vacuole) and long-distance transportation (root to shoot), the two pathways that jointly regulate the content of NO3− in plants. NO3− accumulation within the vacuole depends on the activities of both tonoplast proton pumps and chloride channel (CLC) proteins, and less NO3− is stored in vacuoles when the activities of these proteins are reduced. The ratio of the distribution of NO3− in the cytoplasm and vacuole affects the long-distance transport of NO3−, which is regulated by the proteins NPF7.3 and NPF7.2 that play opposite but complementary roles. NPF7.3 is responsible for loading NO3− from the root cytoplasm into the xylem, whereas NPF7.2 regulates the unloading of NO3− from the xylem, thereby facilitating the long-distance transport of NO3− through the roots to the shoots. Vegetables, valued for their nutrient content, are consumed in large quantities; however, a high content of NO3− can detrimentally affect the quality of these plants. NO3− that is not assimilated and utilized in plant tissues is converted via enzyme-catalyzed reactions to nitrite (NO2−), which is toxic to plants and harmful to human health. In this review, we describe the mechanisms underlying NO3− distribution and transport in plants, a knowledge of which will contribute to breeding leafy vegetables with lower NO3− contents and thus be of considerable significance from the perspectives of environmental protection and food safety.